Aesthetic Sports as High-Risk Contexts for Eating Disorders — Young Elite Dancers and Gymnasts Perspectives - Francisco, Rita (2012)
This is the first study developed in Portugal which investigates specific characteristics of dance and gymnastics environments that make them high-risk contexts for the development of eating disorders. Four focus groups were conducted with thirteen ballet students from a professional dance school and nine gymnasts from a gymnastics club (aged 12 to 17 years old), which were subjected to an inductive-deductive analysis procedure. Specific risk and protective factors were identified. Among their respective sources of influence, teachers and coaches are those who exert a stronger influence upon young athletes. We also explored some themes related to the influence of peers, parents, and environmental characteristics, which could have an important role on the development or prevention of disordered eating.